Advanced Methods Used for the Position and Speed Control of the Electrical Drives with PMSM Motors - SPOIALA Viorica (Journal of Electrical and Electronics Engineering)
The permanent magnet synchronous motor (PMSM) is currently used in advanced electric drive systems of industrial robots, machine tools, electric cars and many others. These complex systems require a precise control of the position and speed of the actuated mechanisms, which presumes the use of the advanced algorithms in this regard. This article presents modern methods such as machine learning, neural networks for controlling the operation of the PMSM motor, which are simulated in a 3D crane system control.